A comparative study of the marketing strategies adopted by the conventional insurers and Islamic insurers / Maznah Wan Omar ... [et al.] - Wan Omar, Maznah; Said, Roshima; Awang, Norasmila; Lope Aman Shah, Sofiah Molek (Universiti Teknologi MARA, Kedah, 2003)
Presently, there are 68 insurers licensed to conduct insurance business in Malaysia. They composed of 58 direct (primary) insurers and 1 0 professional insurers. These insurers operate through 872 branches nation-wide and 1,254 electronic tenninals, set up mostly at the offices of Intermediaries. The Malaysian insurance industry remains largely agencybased with over 122,000 agents registered across the country. The life insurance business is dominated by the foreign-controlled companies, which hold around 78% of the total market share. The local finns dominate the general insurance market, holding a 70% market share, leaving 30% to the foreign controlled companies.